Changing Patterns in Treatment, Remission Status, and Categories in a Long‐Term Nordic Cohort Study of Juvenile Idiopathic Arthritis. Issue 5 (15th March 2022) - Glerup, Mia; Arnstad, Ellen D.; Rypdal, Veronika; Peltoniemi, Suvi; Aalto, Kristiina; Rygg, Marite; Nielsen, Susan; Fasth, Anders; Berntson, Lillemor; Nordal, Ellen; Herlin, Troels; ,
Abstract : Objective: To explore sustainability of achieved remission off medication and defined International League of Associations for Rheumatology (ILAR) categories in juvenile idiopathic arthritis (JIA) and describe the trajectory of disease course over time by comparing treatment, disease activity, and ILAR categories from baseline, 8 years, and 18 years after disease onset. Methods: A total of 373 of the 510 included patients were initially recruited consecutive cases of JIA from the prospective, longitudinal, population‐based Nordic JIA cohort with disease onset during 1997–2000 from Denmark, Norway, Sweden, and Finland in an 18‐year follow‐up study. Clinical data were collected consecutively at baseline, 8 years, and 18 years after disease onset and were evaluated regarding treatment, disease activity, and ILAR category. Results: Significantly more patients (70%) were off medication after 18 years of follow‐up compared to after 8 years (59.7%); nevertheless, the number of patients in remission had not increased (52% off medication versus 51% on medication). Twelve percent of patients changed ILAR category between 8 years and 18 years after disease onset. Almost half of the changes were due to updated information about heredity in a first‐degree relative. In the same period, the psoriatic arthritis group increased significantly in number ( P < 0.001), in contrast to the oligoarticular category, which decreased ( P = 0.02). The undifferentiated group increased 24% from 8 to 18 years of follow‐up; however, this increase was not significant ( P = 0.06). Conclusion: In this Nordic JIA cohort study, the remission rate did not increase even though significantly more patients were off medication at the 18‐year follow‐up compared to at the 8‐year follow‐up after disease onset. The distribution of patients in the ILAR categories continued to change significantly throughout the 18‐year study period.